Conservative treatment of patients with tarsal coalitions - A. V. Sapogoosky; R. Kh. Khusainoo; V. M. Kenis (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
Tarsal coalition is a pathological condition with abnormal fusion between two or more tarsal bones. The aim of the study was to evaluate effectiveness of conservative treatment in patients with tarsal coalitions. The treatment included reducing the intensity of physical activity, medication, orthotics, physiotherapy. For evaluation of effectiveness of the treatment, we used the AOFAS scale. The results of the study demonstrated that conservative treatment in patients with tarsal coalitions was focused onon temporary pain release. Conservative treatment has limited efficacy for patients with symptomatic tarsal coalitions because of short pain release in the majority of children (98 %). The indications for conservative treatment in patients with symptomatic tarsal coalitions should be pain and hindfoot valgus less than 15°. In other cases, conservative treatment should be considered as preoperative preparation.